Expression of hypoxia-inducible factors in human renal cancer: relationship to angiogenesis and to the von Hippel-Lindau gene mutation. - Turner, K; Moore, J; Jones, A; Taylor, C; Cuthbert-Heavens, D; Han, C; Leek, R; Gatter, K; Maxwell, P; Ratcliffe, P; Cranston, D; Harris, A (2002)
The von Hippel-Lindau tumor suppressor protein acts as the substrate recognition component of a ubiquitin E3 ligase that targets hypoxia-inducible factor (HIF)-alpha subunits for proteolysis. Stabilization of HIF-alpha subunits has been described in VHL-defective cell lines, leading to HIF activation and up-regulation of hypoxia-inducible mRNAs. Mutations of the von Hippel-Lindau tumor suppressor protein are found in most clear cell renal cell carcinomas (CC-RCCs) but not other renal tumors, raising a question about the importance of activation of the HIF pathway in CC-RCC development. To address this question, we have examined the expression of HIF-alpha subunits in 45 primary renal tumors and related this to tumor subtype, the presence of VHL mutations, and measures of angiogenesis. We show that HIF-alpha is up-regulated in the majority of CC-RCCs, and that the pattern of expression is biased toward the HIF-2alpha isoform. Expression of HIF-alpha proteins was associated significantly with up-regulation of VEGF mRNA and protein and increased microvessel density. Up-regulation of HIF-alpha in CC-RCC was found to involve increased mRNA as well as protein expression, suggesting that both VHL-dependent and VHL-independent mechanisms are involved. These results suggest that activation of the HIF pathway is functionally important in CC-RCC development and might provide a new therapeutic target.